7‐Deoxynarciclasine shows promising antitumor efficacy by targeting Akt against hepatocellular carcinoma. Issue 12 (23rd May 2019) - Yin, Shuangshuang; Qiu, Yuling; Jin, Chengyun; Wang, Rui; Wu, Song; Liu, Hongwei; Koo, Sangho; Han, Lifeng; Zhang, Yi; Gao, Xiumei; Pang, Xu; Wang, Tao; et al.
Abstract : Akt is a promising therapeutic target for cancer treatment. In our study, we have identified that 7‐deoxynarciclasine (7‐DONCS) is a potential inhibitor of Akt, which results in the repression of multiple oncogenic processes in hepatocellular carcinoma (HCC). We have found that 7‐DONCS suppresses the growth of HCC by inducing the apoptotic and autophagic capacities, as well as by inhibiting epithelial–mesenchymal transition (EMT) in vitro and in vivo . Pretreatment of cells with specific autophagy inhibitor (Bafilomycin A1) or knockdown of endogenous LC‐3B by siRNA strongly abrogates 7‐DONCS‐regulated apoptosis and EMT. Consequently, we have found that 7‐DONCS selectively inhibits phospho‐Akt (Ser473), and subsequent molecular docking reveals that 7‐DONCS directly binds to the C‐terminal domain of Akt. Overexpressing Akt significantly blocks these effects via 7‐DONCS in HCC cells. Furthermore, 7‐DONCS, by targeting Akt, exhibits a promising therapeutic effect in orthotopic hepatocellular tumors. Finally, higher p‐Akt expression is associated with poor prognosis, and higher level of Akt was positively correlated with the enrichment of both apoptosis and autophagy downregulation, and EMT upregulation in HCC patients. These studies suggest that 7‐DONCS serves as an attractive drug candidate by targeting Akt for future HCC therapy. Abstract : What's new? 7‐deoxynarciclasine (7‐DONCS), an active compound isolated from the bulbs of Lycoris radiata (Amaryllidaceae), exhibits various biological effects including anti‐cancer activities. The defined targets or molecular mechanisms underlying 7‐DONCS‐regulated tumorigenesis remain to be unveiled, however. This study elucidates that 7‐DONCS induces apoptosis and autophagy in hepatocellular carcinoma (HCC) and inhibits epithelial‐mesenchymal transition (EMT) by targeting Akt, which in turn prevents tumor growth. The findings indicate that 7‐DONCS may serve as a potential inhibitor of Akt and a promising candidate for blocking tumorigenesis in HCC.